Framing Pemberitaan Dugaan Gratifikasi Kaesang pada Tempo.co dan Kompas.com - Nugroho Dwi Yanto; Razi Muhammad (Comit: Communication, Information and Technology Journal, 2026)
This study analyzes the framing of news coverage of alleged gratification involving Kaesang Pangarep in online media Tempo.co and Kompas.com. Using Robert Entman's framing model, this study aims to reveal how both media frame the issue through four main elements, namely problem definition, cause identification, moral judgment, and resolution recommendations. The results of the analysis show that Tempo.co highlights aspects of uncertainty and procedural challenges, presenting investigative narratives that emphasize the importance of transparency and accountability of state institutions. On the other hand, Kompas.com prioritizes caution by focusing on the family dimension of state administrators, creating a more moderate framing. Both media construct moral messages related to the integrity of public figures and the urgency of clarification to maintain public trust. This study provides insight into the role of the media in shaping public perceptions of legal, ethical, and political issues. These findings are relevant to communication studies, policy makers, and the general public in understanding how the media frames narratives that can influence public opinion.